1997
DOI: 10.1002/(sici)1097-4628(19970418)64:3<553::aid-app12>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Permeability and material characteristics of vulcanized latex film during and following cyclic fatigue in a saline environment

Abstract: ABSTRACT:The importance of stress or fatigue as a source of latex glove failure has been mentioned in several recent studies, but little work has been done to examine the underlying mechanism of these failures. The present work was undertaken to develop techniques for very early detection of structural changes in glove barriers. This was accomplished by monitoring the ion permeability and electrical properties of vulcanized latex glove material during cyclic fatigue in saline. Alteration in the conductance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Dillon and Schroeder confirmed the abovementioned hypothesis visualizing (optic and electron microscope) numerous micro-defects on the surface of the gloves after their two-hour use (25).…”
Section: Latex Glovesmentioning
confidence: 52%
“…Dillon and Schroeder confirmed the abovementioned hypothesis visualizing (optic and electron microscope) numerous micro-defects on the surface of the gloves after their two-hour use (25).…”
Section: Latex Glovesmentioning
confidence: 52%
“…Significant changes in electrical properties were observed by Dillon and Schroeder after ∼117–124 min of fatigue testing; catastrophic rupture appeared about 9 min thereafter. The authors claimed the fatigue lifetime of the latex glove material under the test conditions to be about 2 h 19. These results suggested that a 2‐h creep test would be sufficient.…”
Section: Methodsmentioning
confidence: 96%
“…This load created a 4–6% initial strain that was modest compared to Aggarwal's results for open and closed hands 9. Dillon and Schroeder found that initial strain had an impact on both the fatigue life of the natural rubber and its creep 19. A small initial strain minimizes its impact on subsequent creep.…”
Section: Methodsmentioning
confidence: 99%
“…Physical properties such as puncture resistance, tensile strength, stiffness, and ease of donning for various glove materials have been studied 2, 7, 9, 14, 15. Mechanical durability studies that explore repeated flexing, such as that experienced near the joints and knuckles of a gloved hand while manipulating a sphygmomanometer, as a potential mode of failure for both latex16–19 and nonlatex18, 20 materials have also been performed. The durability studies have shown that repetitive motions, such as flexing, can be detrimental to the barrier properties of medical glove materials.…”
Section: Introductionmentioning
confidence: 99%